2019
DOI: 10.1186/s12866-019-1584-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure and the relationship with soil carbon and nitrogen in an original Korean pine forest of Changbai Mountain, China

Abstract: Background The broad-leaved Korean pine mixed forest is an important and typical component of a global temperate forest. Soil microbes are the main driver of biogeochemical cycling in this forest ecosystem and have complex interactions with carbon (C) and nitrogen (N) components in the soil. Results We investigated the vertical soil microbial community structure in a primary Korean pine-broadleaved mixed forest in Changbai Mountain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 67 publications
3
43
0
1
Order By: Relevance
“…Previous studies have stated that total carbon is a key factor influencing the structure of soil microbial communities. Total carbon has been reported to have substantial direct influence on soil bacterial biomass and it could afford bacteria the benefit of competition with fungal communities for resources [39][40][41]. Phosphorus also affected the structure of the bacterial communities in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies have stated that total carbon is a key factor influencing the structure of soil microbial communities. Total carbon has been reported to have substantial direct influence on soil bacterial biomass and it could afford bacteria the benefit of competition with fungal communities for resources [39][40][41]. Phosphorus also affected the structure of the bacterial communities in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Highly concentrated metals in soil show inhibitory effects on the microorganisms due to dysfunctional microbial processes such as decomposition, and soil respiration [54]. The decrease in microbial count could also be linked with decrease in the concentration of organic carbon required for sustaining microbial growth [55]. However, no specific trend was observed for microbial count at different sites.…”
Section: Effects On Microbiological Properties Of Soilmentioning
confidence: 99%
“…Soil microbial biomass is an essential biological fertility index used to evaluate soil quality [59,60]. Nitrogen and phosphorus de ciency generally have adverse effects on soil microbial reproduction and metabolic activity, as well as on crop growth and nutrient uptake [27,61,62]. The lower MBN and MBP contents in Cry1Ah1-modi ed poplars suggested that soil microorganisms were under nutrient de ciency stress due to low metabolic e ciency and more signi cant release of heat and CO 2 during metabolism, signi cantly reducing soil quality.…”
Section: Changes In Soil Mbc Mbn and Mbp Content In Wt And Cry1ah1-mentioning
confidence: 99%
“…Soil microorganisms are an essential part of the soil ecosystem and are involved in various biochemical processes, including organic matter accumulation and mineralization, as well as nutrient transformation and circulation [23,24]. GM plants communicate with soil microorganisms during the growth process; therefore, research on the potential effects of GM plants on the soil microbial community is of great signi cance in evaluating their potential risks [25][26][27]. The purpose of this study was to identify the effects of Bt-modi ed poplar plantation on soil chemical properties, as well as the diversity and structure of the soil microorganism community after four years of growth under eld conditions.…”
Section: Introductionmentioning
confidence: 99%